Exploring the relationships between visuospatial working memory, math, letter-sound knowledge, motor competence, and gender in first grade children: A correlational study - Eriksen, Adrian Dybfest; Olsen, Alexander; Sigmundsson, Hermundur (Frontiers in Psychology, 2023)
Development of crucial skills accelerates at the start of formal schooling, although, little is known about the relationships between such skills. The current study explored the relationships between visuospatial working memory, letter-sound knowledge, math competence and motor competence, as well as potential effects of gender, in a sample of 85 (42 girls) 6 to 7 years old first grade children. Results demonstrated weak to moderate statistically significant correlations between visuospatial working memory, letter-sound knowledge, math competence, with no statistically significant gender differences. Two motor tasks measuring manual dexterity, placing bricks and building bricks, showed a weak statistically significant correlation. We argue that the findings are supported by the notion of skill specificity. The potential role of visuospatial working memory in procurement of novel skills in early childhood ought to be explored further in future studies.